Recent Developments in Polymer-Based Photonic Components for Disruptive Capacity Upgrade in Data Centers - de Felipe, David; Kleinert, Moritz; Zawadzki, Crispin; Polatynski, Andrzej; Irmscher, Gelani; Brinker, Walter; Moehrle, Martin; Bach, Heinz-Gunter; Keil, Norbert; Schell, Martin (Journal of lightwave technology, 2017)
Recently developed photonic components for nextgeneration datacenter systems based on the Heinrich Hertz Institute's PolyBoard integration platform are reviewed. Hybridintegrated transmitters and receivers, including optical functionalities, such as tunable lasers, polarization manipulators,1 x 2 switches, and variable optical attenuators, are presented. The flexibility of those devices provides the possibility of generating, routing and detecting multiple optical data flows, offering the potential of aggregating traffics of 1 Tb/s and beyond. In addition, vertically stacked polymer waveguide structures are presented, opening the way towards the third dimension in photonic integration and allowing increasing the transmission capacity beyond the physical limit of standard single mode fibers. The freedom in the arrangement of the polymer waveguides allow for the matching of different multicore fiber types, providing the possibility of processing in parallel the different optical flows. By means of micromachining 45° mirrors on the different stack levels, the three-dimensional (3-D) stacked waveguide structure can act as an interface between multicore fibers and planar optoelectronic devices such as photodiodes and laser diodes. Furthermore, a novel concept for a 4 x 4 3-D optical switch based on 3-D multimode interferometers is presented and numerically proven, showing potential for its application as the interface between multicore fibers and planar optoelectronic devices, as well as offering the possibility of reconfigurable N x N switching matrices.